"Political economy of the Southern Africa periphery : cottage industries, factiories and female wage Labour in Swaziland compared" - "Harris, Betty J." (New York, 1993)
This volume places Swazi women workers in the context of the world system at the global, regional and local levels. Issues of race, class and gender are examined by comparative and socio-historical methods. The characteristics and attitudes of Swazi textiles workers in cottage industries and factories are considered. Comparison of these textile workers illuminates the process of stratification of the female labour force in Lesotho, South Africa and Europe. The author has published articles in "Presence Africaine", "Frontiers", "Native American Culture" and "Research Journal".
Keywords: Swaziland - Economic conditions